PERBEDAAN MODEL PEMBELAJARAN INKUIRITRAININGDENGAN MODEL PROBLEM BASED LEARNING ( PBL ) TERHADAP KEMAMPUAN OBSERVASI DALAM KEGIATAN PRAKTIKUM PADA KONSEP SISTEM PENCERNAAN KELAS XIMAN CIAWIGEBANG - Riyanti, Evi; Abidin, Zaenal; Junaedi, Edi (Quagga : Jurnal Pendidikan dan Biologi, 2016)
Research has been carried out with the title "Inquiry learning model differences and Problem Based Learning Training for observation skills in practical activities in the digestive system of class XI material Ciawigebang MAN." This research backgrounds yet many teachers teach subjects with biology lab, so the ability of untrained observation student . This study aimed to determine differences in the students' observation skills through practical activities Inquiry Training Model with Problem Based Learning in the digestive system in class XI material Ciawigebang MAN. Learning model used in this study is a model of Inquiry and Problem Based Learning Training, shape design used in this study is the Group Two posttest design. The population in this study were students of class XI IPA MAN Ciawigebang 2012-2013 academic year consisting of two classes, namely class 1 and class XI Science XI IPA 2 by the number of students 59. In this study sampling was done by cluster random sampling. Indicator rubric of the data, the indicator points 1 the average values obtained Inquiry class training value of 2.10 and an average grade of 2.43 Problem based learning. Wilcoxon test hypothesis test is to find out which one is better on both models on the indicator points 1. Obtained results 9 W count and 111 W table it can be concluded that the indicator points 1 Problem based learning models are better that training inquiry. 2 points on indicators derived average value of 1.79 and a training classroomÂ  inquiry average grade of 1.90 Problem based learning. Wilcoxon test hypothesis test is to find out which one is better in these two models to the indicator points 2. Obtained results 7 W count and 111 W table makadapat concluded that the indicator points 2 Model Problem-based learning is better than training inquiry. Overall rubric of the data obtained for the average value of 4.10 and a training classroom inquiry average grade 4.43 Problem based learning. Test the hypothesis that the value obtained by Wilcoxon test 9 W count and 111 W table. W count W table, which means there is no significant difference between the use of models of inquiry and problem-based learning training on the ability siswadalam practicum observation on the digestive system in class XI matter MAN Ciawigebang with other words Ho accepted and Ha rejected.Keywords: training model of inquiry, problem based learning, observation skills.